(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Metakaolin (MK) is a mineral admixture, various tests are carried out on the usage of Metakaolin for the development of high strength concrete. MK is a supplementary cementitious material derived from heat treatment of natural deposits of kaolin. Metakaolin exhibits high pozzolana reactivity due to their amorphous structure and high surface area. Concrete is the most commonly used material for development of infrastructure. As infrastructure is growing there arises problems in repairs. Due to manufacture of cement, Co2gets emitted into environment. Researches started on working partial replacement of cement, which occur naturallyor manufactured. The different type of pozzolonic materials like metakaolin, silica fume, and fly ash etc, are the material have binding properties that of cement. The present study focuses on replacement cement with metakaolin by 0, 5, 10,15and 20% and fine aggregate with M-sand by 50%.